Energy expenditure and weight-related behaviors in youth with Down syndrome: a protocol - Polfuss, Michele; Bandini, Linda G.; Ravelli, Michele N.; Huang, Zijian; Moosreiner, Andrea; Schoeller, Dale A.; Huang, Chiang-Ching; Ding, Dan; Berry, Cristen; Marston, Emma; Hussain, Azeem; Shriver, Timothy C.; et al. (Frontiers in Pediatrics, 2023)
Background: The consequences of obesity are ominous, yet healthcare professionals are not adequately preventing or treating obesity in youth with Down Syndrome (DS). Total daily energy expenditure (TDEE) is the energy expended in 24 hours through physical activity and life-sustaining physiologic processes. An individual’s TDEE is essential for determining the daily caloric intake needed to maintain or change body weight. Successful prevention and treatment of obesity in youth with DS is severely compromised by the lack of data on TDEE and information on weight-related behaviors for this high-risk population. This manuscript describes the protocol for the federally funded study that is in process to determine daily energy expenditure in a large cohort of children with DS. Methods: This observational cross-sectional study will include a national sample of 230 youth with DS, stratified by age (5-11 and 12-18 years of age) and sex. Doubly Labeled Water analysis will provide the criterion body fat%, fat-free mass, and TDEE. To increase accessibility and decrease the burden on participants, the entire study, including obtaining consent and data collection, is conducted virtually within the participant’s home environment on weekdays and weekends. The study team supervises all data collection via a video conferencing platform, e.g., Zoom. This study will 1) examine and determine average TDEE based on age and sex, 2) develop a prediction equation based on measured TDEE to predict energy requirements with a best-fit model based on fat-free mass, sex, age, and height and/or weight, and 3) use 24-hour dietary recalls, a nutrition and physical activity screener, wearable devices, and sleep questionnaire to describe the patterns and quality of dietary intake, sleep, and physical activity status in youth with DS. Discussion: The lack of accurate information on energy expenditure and weight-related behaviors in youth with DS significantly impedes the successful prevention and treatment of obesity for this vulnerable population. The findings of this study will provide a further understanding of weight-related behaviors as obesity risk factors, currently not well understood for this population. This study will advance the science of weight management in individuals with disabilities and shift clinical practice paradigms.